The Effect of Physical Work Environment, Personality and Fairness on Employee Performance at PT Sinar Jaya - Nasrip, Muhamad; Pono, Nur Fajar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2024)
This study aims to examine the effect of the physical work environment, personality and fairness on employee performance at PT Sinar Jaya. This study uses statistical data with quantitative research, the study population is 130 employees, using probability sampling method with saturated sampling technique. The test analysis uses path analysis with the help of the PLS SEM program. The results of this study state that the physical work environment has no effect and is not significant on employee performance at PT Sinar Jaya, personality has an effect and is significant on employee performance at PT Sinar Jaya and fairness has an effect and significant on employee performance at PT Sinar Jaya. Due to unproven findings in one of the variables, PT Sinar Jaya needs to reorganize by placing employees according to their abilities and always providing ideas to think ahead. For further research, it is necessary to be more specific regarding the indicators used in the physical work environment. It also needs to be re-examined at different agencies by combining other variables that can support the achievement of performance such as non-physical work environment and organizational justice.